Chortkiv district resettlement system and features of transformation in the conditions of administrative and territorial reform - Salii, Mykhailo (Human Geography Journal, 2023)
The article examines the features of the transformation of the Chortkiv inter-district resettlement system into a newly formed district resettlement system, which was formed on the site of six former districts of the southern part of Ternopil Oblast as a result of the administrative-territorial reform. A detailed analysis of the formation of territorial communities of the newly formed Chortkiv district, which arose on the basis of former districts, was carried out. The composition of each community was considered by the number of united councils, the number and type of settlements included in them, the number of cities and villages, as well as the area, population and density of the population, and a comparison was made according to all the indicated indicators between Chortkiv district and in comparison with other communities of Ternopil region. The share of the rural and urban population in each of the communities of the district was analyzed, and the communities where the urban population is the majority and where it is the other way around were determined. By means of cartographic display and comparison of communication routes, the supporting frame of the settlement of Chortkiv district and its place in the general supporting frame of the region were highlighted, and the main cores of population attraction were determined by comparing the places where communication routes intersect and the most densely populated cities and communities. The profitability of transport accessibility between the administrative centers of the district communities was established, the level of transport accessibility between neighboring communities of the district was determined by determining the topographical distances between their administrative centers, as well as the profitability of transport accessibility to the city of Chortkiv from the centers of all communities, and the most and least favorably located settlements were determined.